Sequence Evolution of the Intrinsically Disordered and Globular Domains of a Model Viral Oncoprotein - Chemes, L.B. (2012)
In the present work, we have used the papillomavirus E7 oncoprotein to pursue structure-function and evolutionary studies that take into account intrinsic disorder and the conformational diversity of globular domains. The intrinsically disordered (E7N) and globular (E7C) domains of E7 show similar degrees of conservation and co-evolution. We found that E7N can be described in terms of conserved and coevolving linear motifs separated by variable linkers, while sequence evolution of E7C is compatible with the known homodimeric structure yet suggests other activities for the domain. Within E7N, inter-residue relationships such as residue co-evolution and restricted intermotif distances map functional coupling and co-occurrence of linear motifs that evolve in a coordinate manner. Within E7C, additional cysteine residues proximal to the zinc-binding site may allow redox regulation of E7 function. Moreover, we describe a conserved binding site for disordered domains on the surface of E7C and suggest a putative target linear motif. Both homodimerization and peptide binding activities of E7C are also present in the distantly related host PHD domains, showing that these two proteins share not only structural homology but also functional similarities, and strengthening the view that they evolved from a common ancestor. Finally, we integrate the multiple activities and conformations of E7 into a hierarchy of structure-function relationships. © 2012 Chemes et al.